Role of Workplace Spirituality, Empathic Concern and Organizational Politics in Employee Wellbeing: A Study on Police Personnel - Yadav, Shreshtha; Tiwari, Trayambak; Yadav, Anil Kumar; Dubey, Neha; Mishra, Lalit Kumar; Singh, Anju L.; Kapoor, Payal (Frontiers in Psychology, 2022)
Employee wellbeing as a central aspect of organizational growth has been widely regarded and accepted. Therefore, a considerable growth in the number of researches focusing on employee wellbeing has been comprehended in recent years. Employee wellbeing characterizes the individual's own cognitive interpretation of his/her life at work. The present study made an attempt to examine how workplace spirituality, empathic concern and organizational politics influences employee wellbeing. It was hypothesized that empathic concern mediates the relationship between workplace spirituality and employee wellbeing while organizational politics act as a moderator in this relationship. A survey was conducted on 253 employees working in Uttar Pradesh Police department (Uttar Pradesh, India). The results obtained revealed that workplace spirituality, empathic concern and employee wellbeing carries a positive association among them whereas these variables were found to be negatively correlated with organizational politics. Results also depicted that empathic concern significantly mediates between workplace spirituality and employee wellbeing. Further, moderated mediation analysis confirmed employee wellbeing as a function of workplace spirituality, empathic concern and organizational politics. The present study has put forward several practical implications for business practitioners and research directions for academicians, emphasizing upon the need to investigate the comprehensive impact of employee wellbeing in organization and the society as a whole.